The Effect of Punishment on Discipline of Class VIII Students State Junior High School 1 Juntinyuat Indramayu District - Ahmad Abdul Rochim (PT FORMOSA CENDEKIA GLOBAL, 2023)
The provision of punishment is sought to maintain behaviour by the norms believed by the environment. Discipline is a condition that is created through a process of training and develops into a series of behaviours consisting of elements of obedience, obedience, loyalty, and order. The purpose of the study was to determine the effect of giving punishment to the discipline of class VIII students of SMP Negeri 1 Juntinyuat. This type of research is field research with an associative quantitative design. Data collection techniques are observation, questionnaires and documentation with descriptive and inferential analysis techniques. The results showed: (1) The provision of punishment was in the good category with a figure of 77.4%. (2) Student discipline is in the good category with a figure of 85.4%. (3) There is a significant effect between giving punishment to the discipline of class VIII students of SMP Negeri 1 Juntinyuat.